Structure-function-guided exploration of the antimicrobial peptide polybia-CP identifies activity determinants and generates synthetic therapeutic candidates. (December 2018) - Torres, Marcelo; Pedron, Cibele; Higashikuni, Yasutomi; Kramer, Robin; Cardoso, Marlon; Oshiro, Karen; Franco, Octávio; Silva Junior, Pedro; Silva, Fernanda; Oliveira Junior, Vani; Lu, Timothy; de la Fuente-Nunez, Cesar
Abstract Antimicrobial peptides (AMPs) constitute promising alternatives to classical antibiotics for the treatment of drug-resistant infections, which are a rapidly emerging global health challenge. However, our understanding of the structure-function relationships of AMPs is limited, and we are just beginning to rationally engineer peptides in order to develop them as therapeutics. Here, we leverage a physicochemical-guided peptide design strategy to identify specific functional hotspots in the wasp-derived AMP polybia-CP and turn this toxic peptide into a viable antimicrobial. Helical fraction, hydrophobicity, and hydrophobic moment are identified as key structural and physicochemical determinants of antimicrobial activity, utilized in combination with rational engineering to generate synthetic AMPs with therapeutic activity in a mouse model. We demonstrate that, by tuning these physicochemical parameters, it is possible to design nontoxic synthetic peptides with enhanced sub-micromolar antimicrobial potency in vitro and anti-infective activity in vivo. We present a physicochemical-guided rational design strategy to generate peptide antibiotics. Marcelo D. T. Torres et al. turn toxic wasp-derived antimicrobial peptide polybia-CP into a viable antimicrobial with therapeutic activity in a mouse model. This study demonstrates that a physicochemical property-guided rational design strategy can be used to generate peptide antibiotics.